(untitled) (Research, Society and Development, 2022)
This study is a part of the research work that was carried out to compose the master’s thesis "Analysis of school dropout in EJA and a proposal for teaching Mathematics aiming at the students’ permanence". It aims to investigate the situations that relate to the occurrence of school dropout in EJA. Addresses school dropout and/or truancy in the Early and Final Years of Elementary and high school EJA students, from a national perspective in the period between 2011 and 2020, resorting to bibliographical research, exploring the CAPES database. For the literature review, the steps of the Integrative Review are used and the data analysis methodology follows the qualitative approach, being interpreted through Content Analysis. For situations related to the occurrence of dropout in EJA, two categories emerge as results: EJA dropout causes external to school (subcategories: social and financial; emotional or health; personal or family) and EJA dropout causes internal to school (subcategories: socialization; organization of daily school life or pedagogical practice; government action with the school). The conclusions show that school dropout is a complex problem, which needs to be analyzed from several aspects and when it comes to Youth and Adult Education, it requires that the specificities of these students are recognized, in order that the actions can express the need to stay at school.